Active Surveillance of Small Renal Masses: A Review on the Role of Imaging With a Focus on Growth Rate. Issue 4 (July 2016) - Nayyar, Megha; Cheng, Phillip; Desai, Bhushan; Cen, Steven; Desai, Mihir; Gill, Inderbir; Duddalwar, Vinay
Abstract : Objective: This study aimed to systematically summarize the current literature in the field of active surveillance for small renal masses, with the primary focus being the role of imaging in the primary decision-making and subsequent follow-up. Materials: A systematic review of the electronic databases PubMed and Web of Knowledge was performed according to Preferred Reporting Items for Systematic Reviews and Meta-analysis statement guidelines. Variables were extracted from the data set and included the following: (1) patient demographics, (2) tumor characteristics, and (3) study design. Results: Twenty-one articles studying imaging in active surveillance of small renal masses were selected. Seventy-two percent (15/21) of studies were retrospective; 19% (4/21) were prospective; and 9% (2/21) studies were bidirectional. Mean age of patients was 69 years (range, 57–81 years). A total of 1386 patients were in the study; 59% of patients were men. Mean follow-up was 39 months (range, 18.8–91.5 months). Sixty-seven percent of masses discussed in this review were followed up using more than one imaging modality; 19% consistently used computed tomography for follow-up whereas the remaining 14% did not specify what imaging modality was used. Imaging studies were reviewed by the investigators centrally in 86% (18/21). In 14% of the studies, only imaging report was reviewed. Biopsy was performed in 24% of masses. Mean growth rate for all tumors was 0.27 cm/y (range, 0.06–0.7 cm/y). For studies where growth rate of benign and malignant masses were differentiated, mean growth rate for benign masses was 0.3 cm/y and mean growth rate for malignant masses was 0.35 cm/y. Conclusions: Growth rate is often used as a discriminant in following up a small renal mass in patients undergoing active surveillance. However, there is great variability in growth rate and it alone is not an adequate marker for determining whether the tumor is malignant. Because very few studies specified radiological characteristics of small renal masses, future studies can be done to better characterize masses.